Efficacy of probiotics in acute diarrhoea in children - Bhat, Sinchana; G. N., Shreekrishna; Savio, Christi D. (International Journal of Contemporary Pediatrics, 2018)
Background: Gastroenteritis is a major public health problem worldwide and remains the second leading cause of death among children under five globally. Objective of this study was to investigate and compare the efficacy of commonly available probiotics in the treatment of acute watery diarrhoea (AWD) in children. Methods: This was an open label randomised controlled trial conducted in a tertiary care hospital in Bangalore for 2 years. 120 children aged 6 months to 5 years admitted with AWD of less than or equal to 48 hours duration were randomized into three groups – Group I (control) received oral rehydration therapy and zinc, Group II received Bacillus clausii in a dose of 2 billion spores twice a day and Group III received Saccharomyces boulardii as 250 mg twice a day. The primary outcome measures were total duration of diarrhoea, mean number of stools per day, consistency of stools and secondary outcome measures were duration of vomiting, fever and hospital stay. ANOVA, Student t test, Mann Whitney U test and Chi square test were used for analysis. Results: The duration of diarrhoea and hospital stay significantly reduced (41.68 hrs) in Group III compared to Group I (57.65 hrs) and Group II (53.33 hrs). (p< 0.05). The frequency of stools reduced significantly on Day 4 and the consistency of stools improved significantly on Day 3 in both the probiotic groups (p<0.05). Both the probiotics reduced the duration of fever significantly but had no effect on the duration of vomiting. Conclusions: Saccharomyces boulardii is effective in reducing the duration of diarrhea and hospital stay in children with acute gastroenteritis.